2015
DOI: 10.1111/jfb.12685
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐population ovarian fluid variation differentially modulates sperm motility in Atlantic cod Gadus morhua

Abstract: This study tested the hypothesis that the effects of Atlantic cod Gadus morhua ovarian fluid on sperm motility variables are population specific. Sperm from a northern G. morhua population were activated in the presence of ovarian fluid from either northern or southern G. morhua at different concentrations. Ovarian fluid acted as a filter, in some cases reducing sperm swimming performance compared with seawater. Fluid from females foreign in population (southern) to the males (northern) had a greater inhibitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…To our knowledge, the only study to date that has explicitly investigated a possible role of PEMS in reproductive isolation has been with the congeneric fish, Salmo salar and S. trutta . Ovarian fluid composition is highly divergent in fish, exhibiting substantial differences among species (Lahnsteiner, Weismann, & Patzner, ) and even between members of different geographic populations within species (Beirão et al ., ). Studies comparing ovarian fluid‐induced modification to sperm exposed to ovarian fluid derived from the either the same or different populations or congeneric species provide strong support for the conclusion that ovarian fluid composition and interacting sperm traits are evolutionarily co‐diversifying (Yeates et al ., ; Beirão et al ., ; Devigili et al ., ).…”
Section: Evolutionary Implications Of Pemsmentioning
confidence: 97%
“…To our knowledge, the only study to date that has explicitly investigated a possible role of PEMS in reproductive isolation has been with the congeneric fish, Salmo salar and S. trutta . Ovarian fluid composition is highly divergent in fish, exhibiting substantial differences among species (Lahnsteiner, Weismann, & Patzner, ) and even between members of different geographic populations within species (Beirão et al ., ). Studies comparing ovarian fluid‐induced modification to sperm exposed to ovarian fluid derived from the either the same or different populations or congeneric species provide strong support for the conclusion that ovarian fluid composition and interacting sperm traits are evolutionarily co‐diversifying (Yeates et al ., ; Beirão et al ., ; Devigili et al ., ).…”
Section: Evolutionary Implications Of Pemsmentioning
confidence: 97%
“…Beside species‐specific differences, such variances in the composition of CF can be related to changes in a female's physiological status throughout the spawning season, as well as with changes in egg quality and maturity (Aegerter & Jalabert, ; Lahnsteiner, ; Lahnsteiner, Weismann, & Patzner, ). Beirão, Purchase, Wringe, and Fleming () also reported an inter‐population variation in the concentration of Ca ++ of CF that differentially modulates sperm motility in Atlantic cod Gadus morhua . The CFs of different sturgeon species in the present study were alkaline, as reported for cyprinids and salmonids (Hatef et al., ; Hirano, Morisawa, & Suzuki, ; Lahnsteiner, Urbanyi, Horvath, & Weismann, ; Niksirat, Sarvi, Mojazi Amiri, & Hatef, ; Niksirat, Sarvi, Mojazi Amiri, Karami, & Hatef, ).…”
Section: Discussionmentioning
confidence: 92%
“…testing more than two populations, from a range of geographical origins). However, our results are in line with previous studies that evaluated the presence of similar reproductive barriers acting among (Yeates et al ., ; Cramer et al ., ) and within species (Beirao et al ., ). Nevertheless, our findings indicate some complexity in the observed patterns at the within‐species level, where the direction of the effect depended on the specific combination of populations examined.…”
Section: Discussionmentioning
confidence: 97%